Cardiovascular phenotype of the Dmdmdx rat - a suitable animal model for Duchenne muscular dystrophy - Petra Lujza Szabó; Janine Ebner; Xaver Koenig; Ouafa Hamza; Simon Watzinger; Sandra Trojanek; Dietmar Abraham; Hannes Todt; Helmut Kubista; Klaus Schicker; Séverine Remy; Ignacio Anegon; et al. (The Company of Biologists, 2021)
Besides skeletal muscle abnormalities, Duchenne muscular dystrophy (DMD) patients present with dilated cardiomyopathy development, which considerably contributes to morbidity and mortality. Because the mechanisms responsible for the cardiac complications in the context of DMD are largely unknown, evidence-based therapy approaches are still lacking. This has increased the need for basic research efforts into animal models for DMD. Here, we characterized in detail the cardiovascular abnormalities of Dmdmdx rats, with the aim of determining the suitability of this recently established dystrophin-deficient small animal as a model for DMD. Various methods were applied to compare cardiovascular properties between wild-type and Dmdmdx rats, and to characterize the Dmdmdx cardiomyopathy. These methods comprised echocardiography, invasive assessment of left ventricular hemodynamics, examination of adverse remodeling and endothelial cell inflammation, and evaluation of vascular function, employing wire myography. Finally, intracellular Ca2+ transient measurements, and recordings of currents through L-type Ca2+ channels were performed in isolated single ventricular cardiomyocytes. We found that, similar to respective observations in DMD patients, the hearts of Dmdmdx rats show significantly impaired cardiac function, fibrosis and inflammation, consistent with the development of a dilated cardiomyopathy. Moreover, in Dmdmdx rats, vascular endothelial function is impaired, which may relate to inflammation and oxidative stress, and Ca2+ handling in Dmdmdx cardiomyocytes is abnormal. These findings indicate that Dmdmdx rats represent a promising small-animal model to elucidate mechanisms of cardiomyopathy development in the dystrophic heart, and to test mechanism-based therapies aiming to combat cardiovascular complications in DMD.